2007
DOI: 10.1177/1359105307082458
|View full text |Cite
|
Sign up to set email alerts
|

Personality, Emotional Intelligence and Exercise

Abstract: The associations of personality and self-report emotional intelligence (EI) with attitudes to exercise and self-reported exercise behaviour were investigated in a sample of 497 Canadian undergraduates. A positive attitude to exercise was negatively associated with Neuroticism and uncorrelated with other personality traits and EI. Exercise behaviour was positively associated with Extraversion and EI and negatively associated with Neuroticism. Structural equation modelling indicated that EI mediated the relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
56
1
12

Year Published

2009
2009
2022
2022

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 83 publications
(82 citation statements)
references
References 41 publications
(74 reference statements)
13
56
1
12
Order By: Relevance
“…There are a few previous researches supported the findings in this study. Saklofske et al (2007) well supported this study's findings as EI has positively correlated with positive psychological wellbeing such as life satisfaction and happiness while, EI has negatively correlated with negative psychological well-being such as depression, stress and loneliness. Equally, Lougheed and Hollenstein (2012) reported that high range of emotional regulation lowered the internalizing problems such as depression, anxiety and social anxiety while lower range of emotional regulation increased internalizing problems in adolescents.…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…There are a few previous researches supported the findings in this study. Saklofske et al (2007) well supported this study's findings as EI has positively correlated with positive psychological wellbeing such as life satisfaction and happiness while, EI has negatively correlated with negative psychological well-being such as depression, stress and loneliness. Equally, Lougheed and Hollenstein (2012) reported that high range of emotional regulation lowered the internalizing problems such as depression, anxiety and social anxiety while lower range of emotional regulation increased internalizing problems in adolescents.…”
Section: Discussionsupporting
confidence: 77%
“…Some of the previous research supported the findings in this study. Saklofske et al (2007) found that there was a relationship between exercise and EI by stating the effect of exercise towards social and mood regulation. Moreover, it was also supported by Li et al (2009) as they found that higher level of PA will lead students to have more positive mood, optimistic attitude and lowering negative mood.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations